A power-control interference management mechanism for Femtocell-based networks. (2018) - Salameh, Haythem A. Bany; Shabbar, Rawan; Alshamali, Ahmad
Femtocell deployment is one of the promising solutions to meet the increasing demands on wireless services and applications. Based on deploying Femtocells within the already-existing Macrocells, Femtocells can improve indoor coverage and increase both spectral efficiency and data rate. This improvement can be achieved by reusing the available spectrum assigned for the Macrocells, and being closer to the users. However, Femtocell deployment faces many challenges. One of the most challenging issues is the interference management issue. In this paper, a power-control channel assignment algorithm to manage the interference between Femtocell and Macrocell networks is proposed. The proposed algorithm allows frequency reuse among Femtocell users (FUEs) to provide better throughput performance. Simulation results have shown an improvement in throughput by up to 90% compared to previous schemes.